Preparation and characterization of titania-cyanopropyltriethoxysilane sorbent for the extraction of polar aromatic amines - Miskam, Mazidatulakmam; Abu Bakar, Nor Kartini; Mohamad, Sharifah (Springer Science+Business Media New York, 2015)
A new titanium(IV) butoxide-cyanopropyltriethoxysilane (Ti-CNPrTEOS) hybrid material was successfully synthesized for the use as sorbent for the extraction of polar aromatic amines. The sorbent was synthesized by hydrolysis and condensation of titanium(IV) butoxide and cyanopropyltriethoxysilane with the presence of hydrochloric acid as catalyst via sol–gel method. Several factors influencing the synthesized sorbent such as solvent selection, mol of water content, ratio of titanium(IV) butoxide and cyanopropyltriethoxysilane and aging temperature were investigated and optimized. The sorbents were characterized by fourier transform-infrared, field-emission scanning electron microscopy-energy, CHN elemental analysis and thermogravimetric analysis. The applicability of the sorbents for the extraction of polar aromatic amines by the batch sorption method was extensively studied and evaluated. Under the optimum synthesis conditions (tetrahydrofuran as solvent, 1.2 M of hydrochloric acid catalyst, 4 mol of water content with ratio of titanium(IV) butoxide and cyanopropylteriethoxysilane of 1:1 and aging temperature of 60 C), the extraction showed high recovery towards the extraction of polar aromatic amines. The synthesized sorbent was successfully applied for the extraction of selected aromatic amines via batch sorption method in waste water samples prior to the gas chromatography-flame ionization detector separation. The synthesized sol–gel Ti-CNPrTEOS sorbent demonstrated the potential as an alternative extraction sorbent with higher selectivity towards polar aromatic amines.